La lectura insumisa. Texto e ilustración en los clásicos Billiken para las niñas - Amanda Salvioni (Confluenze, 2022)
The article focuses on the relationship between image and text in children's illustrated books. Some classics of Latin American literature adapted for children are analyzed in the framework of the Biblioteca Billiken published in Argentina, between the 1940s and 1980s of the 20th century, especially designed for girls. The pedagogical and protective vocation of the collection and its conservative orientation within the Argentine publishing scene seems to be attenuated thanks to the presence of the illustrations, which gives rise to a potential way of reading less linked to the order of the discourse.